Pour une nouvelle politique des études littéraires francophones
During the past decades, francophone literary studies emerged on the international academic field. This paper aims to look back at a few aspects of these developments. Our hypothesis is that these studies first contributed to build a representation of “francophone literature” very close to the diplomatic “Francophonie” project, then tried to perform both theoretically and politically (our examples will be the “gravitational model” and the postcolonial paradigm). The reflux of the “overlooking position” which defines these approaches brings us to question the new ways to commit literary studies with politics (in Stanley Fish and Yves Citton), by focusing on the rhetorical and ideological operations in the discourses about literature.